The Internationalization Process of International New Ventures: The Case of Skype - Chan, Cheuk-Hay (2007)
Past literature has emphasized on large, long-established multinational enterprises (MNEs) in international business. However, the emerging phenomenon of international new ventures has attracted much attention due to their distinctive internationalization processes. Skype Technologies S.A. is one of these international new ventures with comparable characteristics, albeit it has shown differences compared with the typical international new ventures. This research aims to compare and contrast the features between traditional multinational enterprises, typical international new ventures and the case of Skype with emphasis on their internationalization processes and competitive advantages.